Hydrothermal Carbonization of Sludge Residues via Carborem C700 Industrial Scale Continuous Operating Plant - Michela Lucian; Fabio Merzari; Antonio Messineo; Maurizio Volpe (Chemical Engineering Transactions, 2022)
This study describes the main features of a novel industrial-scale continuous operating hydrothermal carbonization (HTC) developed by Carborem srl named C700. The C700 industrial-scale HTC plant is a highly compact, modular and containerized system capable of treating more than 5 kton per year of sludge. The results of HTC operated with C700 plant at 190 °C and 1 h of residence time of three different high moisture content residues (sewage sludge, agro-industrial sludge, and organic fraction of municipal solid waste digestate) demonstrate the efficiency and versatility of the process. C700 system is capable of promoting dewaterability of sludge residues, producing solid residues (hydrochars) upon centrifugation of HTC slurries with improved phosphorus content. Results show that the system allows concentrating P into the solid residue up to 3.6 wt% on a dry basis and leads to hydrochars with a total solid content, upon centrifugation of 34.6, 38.6 and 41.0 wt% for sewage and agro-industrial sludge and organic fraction of municipal solid waste digestate, respectively. Moreover, while hydrochars show good potential as soil fertilizers, when excess heavy metals like copper and zinc are removed, recirculation of the high carbon content liquid residue to the anaerobic digestion system offers the opportunity to enhance biogas production in the waste management plant thus lowering the total external energy demand of the process.